Konsep Pengembangan Kebun Raya Balikpapan Sebagai Destinasi Wisata Alam Unggulan - Rizky Arif Nugroho; Elin Diyah Syafitri; Rahmi Yorika (Jurnal Pembangunan Wilayah dan Kota, 2021)
Balikpapan Botanical Garden, which was established in 1994, held potential to be developed more. It was possible since Balikpapan Botanical Garden had 300 hectare wide area. The development of Balikpapan Botanical Garden supported East Kalimantan Government plan to enhanced their tourism sector. Therefore, the concept of Balikpapan Botanical Garden development was necessary. By using descriptive qualitative analysis, the concept formulated as followed. Ensuring safety and security of tourist, creating special zone for interaction between tourist and nature, holding event, providing transportation mode, and deploying trained and professional staff.